Business Analytics Capabilities for Data Driven E-commerce: Potential Research Directions - Bahjat FAKIEH (Communications of International Proceedings, 2025)
Business Analytics is an field of knowledge that analyzes and understands data in order to assist organizations and decision makers to improve their decisions and to lead to better business outcomes. Those organizations include public, private and non-profit sectors regardless of their size, revenue, or any other factors. E-commerce has several opportunities to harness the significance of business analytics due to the business nature of digital systems and data availability. This study aims to explore the capabilities and the possible research directions in business analytics area to support the maturity of having data driven e-commerce. It also highlights the common challenges that could affect the streamlining of the process. It starts by highlighting the broad categories of business analytics to absorb the main research directions in this area. Then, business analytics applications were discussed briefly to show some of its capabilities to drive enterprises. After that, business analytics practices in the e-commerce environment were discussed to shed light on the possible research directions, that is followed by discussing the common Business analytics challenges that researchers should be aware of. The contribution of this study emphasis the potential of utilizing business analytics as core research by itself or in conjunction with several areas of knowledge to provide useful data driven insights and to drive business outcomes. In addition, the study summarizes several challenges could encounter researchers, and one of the major challenges is the availability of the required data.
Keywords: Analytics; Business Analytics; Data; Decision Making; e-commerce.